Photosynthesis of Quercus suber is affected by atmospheric NH3 generated by multifunctional agrosystems - Pintó-Marijuan, Marta; Da Silva, Anabela Bernardes; Flexas, Jaume; Dias, Teresa; Zarrouk, Olfa; Martins-Loução, Maria Amélia; Chaves, Maria Manuela; Cruz, Cristina (Tree Physiology, 2013)
Montados are evergreen oak woodlands dominated by Quercus species, which are considered to be key to biodiversity conservation and ecosystem services. This ecosystem is often used for cattle breeding in most regions of the Iberian Peninsula, which causes plants to receive extra nitrogen as ammonia (NH3) through the atmosphere. The effect of this atmospheric NH3 (NH3atm) on ecosystems is still under discussion. This study aimed to evaluate the effects of an NH3atm concentration gradient downwind of a cattle barn in a Montado area. Leaves from the selected Quercus suber L. trees along the gradient showed a clear influence of the NH3 on δ13C, as a consequence of a strong limitation on the photosynthetic machinery by a reduction of both stomatal and mesophyll conductance. A detailed study of the impact of NH3atm on the photosynthetic performance of Q. suber trees is presented, and new mechanisms by which NH3 affects photosynthesis at the leaf level are suggested.
10.1093/treephys/tpt077
Keywords: carbon isotopic discrimination; Cork oak; mesophyll conductance; Stomatal conductance

Do photosynthetic limitations of evergreen Quercus ilex leaves change with long-term increased drought severity? - Limousin, Jean-Marc; Misson, Laurent; LAVOIR, ANNE-VIOLETTE; MARTIN, NICOLAS K.; Rambal, Serge (Plant, Cell & Environment, 2010)
Seasonal drought can severely impact leaf photosynthetic capacity. This is particularly important for Mediterranean forests, where precipitation is expected to decrease as a consequence of climate change. Impacts of increased drought on the photosynthetic capacity of the evergreen Quercus ilex were studied for two years in a mature forest submitted to long-term throughfall exclusion. Gas exchange and chlorophyll fluorescence were measured on two successive leaf cohorts in a control and a dry plot. Exclusion significantly reduced leaf water potential in the dry treatment. In both treatments, light-saturated net assimilation rate (Amax), stomatal conductance (gs), maximum carboxylation rate (Vcmax), maximum rate of electron transport (Jmax), mesophyll conductance to CO2 (gm) and nitrogen investment in photosynthesis decreased markedly with soil water limitation during summer. The relationships between leaf photosynthetic parameters and leaf water potential remained identical in the two treatments. Leaf and canopy acclimation to progressive, long-term drought occurred through changes in leaf area index, leaf mass per area and leaf chemical composition, but not through modifications of physiological parameters.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: acclimation; Drought; Mediterranean evergreen; mesophyll conductance; photo- synthetic capacity; photosynthesis limitation; Seasonality; throughfall exclusion

The importance of mesophyll conductance in regulating forest ecosystem productivity during drought periods - KEENAN, Trevor; Sabaté, Santi; Gracia, Carlos (Global Change Biology, 2010)
Water availability is the most limiting factor to global plant productivity, yet photosynthetic responses to seasonal drought cycles are poorly understood, with conflicting reports on which limiting process is the most important during drought. We address the problem using a model-data synthesis approach to look at canopy level fluxes, integrating twenty years of half hour data gathered by the FLUXNET network across six Mediterranean sites. The measured canopy level, water and carbon fluxes were used, together with an inverse canopy ecophysiological model, to estimate the bulk canopy conductance, bulk mesophyll conductance, and the canopy scale carbon pools in both the intercellular spaces and at the site of carboxylation in the chloroplasts. Thus the roles of stomatal and mesophyll conductance in the regulation of internal carbon pools and photosynthesis could be separated. A quantitative limitation analysis allowed for the relative seasonal responses of stomatal, mesophyll, and biochemical limitations to be gauged. The concentration of carbon in the chloroplast was shown to be a potentially more reliable estimator of assimilation rates than the intercellular carbon concentration. Both stomatal conductance limitations and mesophyll conductance limitations were observed to regulate the response of photosynthesis to water stress in each of the six species studied. The results suggest that mesophyll conductance could bridge the gap between conflicting reports on plant responses to soil water stress, and that the inclusion of mesophyll conductance in biosphere–atmosphere transfer models may improve their performance, in particular their ability to accurately capture the response of terrestrial vegetation productivity to drought.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: 16 june 2009; conductance limitations; Drought; FLUXNET; june 2009 and accepted; Mediterranean climate; mesophyll conduc-; mesophyll conductance; photosynthesis; received 12 march 2009; revised version received 2; tance; water stress

Mesophyll conductance to CO2 and leaf morphological characteristics under drought stress during Quercus ilex L. resprouting - Fleck, Isabel; Peña-Rojas, Karen; Aranda, Xavier (Annals of Forest Science, 2010)
• Quercus ilex L., the dominant species in Mediterranean forests and one with a great capacity for resprouting after disturbances, is threatened by the expected increase in ﬁre frequency and drought associated with climate change. • The aim of this study was to determine the contribution of photosynthesis limitants, especially mesophyll conductance (gmes ) during this species’ resprouting and under summer drought. • Resprouts showed 5.3-fold increased gmes and 3.8-fold increased stomatal conductance (gs ) at midday with respect to leaves of undisturbed individuals. With increased drought, structural changes (decreased density and increased thickness) in resprouts contributed to the observed higher photosynthesis and increased gmes . However, gmes only partially depended on leaf structure, and was also under physiological control. Resprouts also showed lower non-stomatal limitations (around 50% higher carboxylation velocity (Vc,max) and capacity for ribulose-1,5-bisphosphate regeneration (Jmax)). A signiﬁcant contribution of gmes to leaf carbon isotope discrimination values was observed. • gmes exhibits a dominant role in photosynthesis limitation in Q. ilex and is regulated by factors other than morphology. During resprouting after disturbances, greater capacity to withstand drought, as evidenced by higher gmes , gs and lower non-stomatal limitants, enables increased photosynthesis and rapid growth.
Keywords: carbon isotopic composition; leaf structure; mesophyll conductance; photosynthesis limitants; Quercus ilex

Complex adjustments of photosynthetic potentials and internal diffusion conductance to current and previous light availabilities and leaf age in Mediterranean evergreen species Quercus ilex - NIINEMETS, Ü L O; CESCATTI, ALESSANDRO; RODEGHIERO, MIRCO; TOSENS, TIINA (Plant, Cell & Environment, 2006)
Mature non-senescent leaves of evergreen species become gradually shaded as new foliage develops and canopy expands, but the interactive effects of integrated light during leaf formation (QintG), current light (QintC) and leaf age on foliage photosynthetic competence are poorly understood. In Quercus ilex L., we measured the responses of leaf structural and physiological variables to QintC and QintG for four leaf age classes. Leaf aging resulted in increases in leaf dry mass per unit area (MA), and leaf dry to fresh mass ratio (DF) and decreases in N content per dry mass (NM). N content per area (NA) was independent of age, indicating that decreases in NM reflected dilution of leaf N because of accumulation of dry mass (NA = NM MA). MA, DF and NA scaled positively with irradiance, whereas these age-specific correlations were stronger with leaf growth light than with current leaf light. Area-based maximum ribulose 1,5-bisphosphate carboxylase/oxygenase (Rubisco) carboxylase activity (VcmaxA), capacity for photosynthetic electron transport (JmaxA) and the rate of non-photorespiratory respiration in light (RdA) were also positively associated with irradiance. Differently from leaf structural characteristics, for all data pooled, these relationships were stronger with current light with little differences among leaves of different age. Acclimation to current leaf light environment was achieved by light-dependent partitioning of N in rate-limiting proteins. Mass-based physiological activities decreased with increasing leaf age, reflecting dilution of leaf N and a larger fraction of non-photosynthetic N in older leaves. This resulted in age-dependent modification of leaf photosynthetic potentials versus N relationships. Internal diffusion conductance (gm) per unit area (gmA) increased curvilinearly with increasing irradiance for two youngest leaf age classes and was independent of light for older leaves. In contrast, gm per dry mass (gmM) was negatively associated with light in current-year leaves. Greater photosynthetic potentials and moderate changes in diffusion conductance resulted in greater internal diffusion limitations of photosynthesis in higher light. Both area- and mass-based gm decreased with increasing leaf age. The decrease in diffusion conductance was larger than changes in photosynthetic potentials, leading to larger CO2 drawdown from leaf internal air space to chloroplasts (ΔC) in older leaves. The increases in diffusion limitations in older leaves and at higher light scaled with age- and light-dependent increases in MA and DF. Overall, our study demonstrates a large potential of foliage photosynthetic acclimation to changes in leaf light environment, but also highlights enhanced structural diffusion limitations in older leaves that result from leaf structural acclimation to previous rather than to current light environment and accumulation of structural compounds with leaf age.
Keywords: CO2 drawdown; growth irradiance; leaf age; leaf structure; mesophyll conductance; nitrogen content; photosynthetic capacity

Complex adjustments of photosynthetic potentials and internal diffusion conductance to current and previous light availabilities and leaf age in Mediterranean evergreen species Quercus ilex - NIINEMETS, Ü L. O.; CESCATTI, ALESSANDRO; RODEGHIERO, MIRCO; TOSENS, TIINA (Plant, Cell & Environment, 2006)
Mature non-senescent leaves of evergreen species become gradually shaded as new foliage develops and canopy expands, but the interactive effects of integrated light during leaf formation (QintG), current light (QintC) and leaf age on foliage photosynthetic competence are poorly understood. In Quercus ilex L., we measured the responses of leaf structural and physiological variables to QintC and QintG for four leaf age classes. Leaf aging resulted in increases in leaf dry mass per unit area (MA), and leaf dry to fresh mass ratio (DF) and decreases in N content per dry mass (NM). N content per area (NA) was independent of age, indicating that decreases in NM reflected dilution of leaf N because of accumulation of dry mass (NA = NM MA). MA, DF and NA scaled positively with irradiance, whereas these age-specific correlations were stronger with leaf growth light than with current leaf light. Area-based maximum ribulose 1,5-bisphosphate carboxylase/oxygenase (Rubisco) carboxylase activity (VcmaxA), capacity for photosynthetic electron transport (JmaxA) and the rate of non-photorespiratory respiration in light (RdA) were also positively associated with irradiance. Differently from leaf structural characteristics, for all data pooled, these relationships were stronger with current light with little differences among leaves of different age. Acclimation to current leaf light environment was achieved by light-dependent partitioning of N in rate-limiting proteins. Mass-based physiological activities decreased with increasing leaf age, reflecting dilution of leaf N and a larger fraction of non-photosynthetic N in older leaves. This resulted in age-dependent modification of leaf photosynthetic potentials versus N relationships. Internal diffusion conductance (gm) per unit area (gmA) increased curvilinearly with increasing irradiance for two youngest leaf age classes and was independent of light for older leaves. In contrast, gm per dry mass (gmM) was negatively associated with light in current-year leaves. Greater photosynthetic potentials and moderate changes in diffusion conductance resulted in greater internal diffusion limitations of photosynthesis in higher light. Both area- and mass-based gm decreased with increasing leaf age. The decrease in diffusion conductance was larger than changes in photosynthetic potentials, leading to larger CO2 drawdown from leaf internal air space to chloroplasts (ΔC) in older leaves. The increases in diffusion limitations in older leaves and at higher light scaled with age- and light-dependent increases in MA and DF. Overall, our study demonstrates a large potential of foliage photosynthetic acclimation to changes in leaf light environment, but also highlights enhanced structural diffusion limitations in older leaves that result from leaf structural acclimation to previous rather than to current light environment and accumulation of structural compounds with leaf age.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: CO2 drawdown; growth irradiance; leaf age; leaf structure; mesophyll conductance; nitrogen content; photosynthetic capacity

Limitation of photosynthetic activity by CO2 availability in the chloroplasts of oak leaves from different species and during drought - Roupsard, O; Gross, P; Dreyer, E (Ann. For. Sci., 1996)
It has recently been suggested that the low photosynthesis rates in tree species as compared to highly productive crops is at least partly due to resistances opposing the CO 2 fluxes in the mesophyll of tree leaves. To validate this assertion, values of CO2 mole fractions in the chloroplasts of leaves from Quercus petraea, Q robur, Q ilex and Populus sp were estimated on the basis of the analysis of the partitioning of light driven electron flow between fractions used for the carboxylation or the oxygenation of RuBP by Rubisco. The procedure used included: i) a measure of total light driven electron flows derived from the chlorophyll a fluorescence ratio ΔF/Fm', which is proportional to the photochemical efficiency of PS II, multiplied by incident irradiance and a calibration coefficient; ii) an estimation of the electron flux devoted to carboxylation obtained from net CO2 assimilation and respiration rate measurement, and using the known electron requirements (four electrons for CO2 or O2 fixation); iii) the derivation of the CO2 mole fraction in the chloroplasts from the specificity factor of Rubisco, and the ratio of carboxylation/oxygenation of RuBP. Results showed that in the absence of drought stress, the mole fraction of CO2 in the chloroplasts (35-45% of the atmospheric one) was much lower than the calculated substomatal one (60-70% of the atmospheric) in all species. Moreover, lowest values were recorded in the species with lowest assimilation rates, suggesting that the differences in the net CO 2 assimilation rate between species are linked to the CO2 availability in the chloroplasts. Finally, the CO2 availability decreased with increasing drought in the soil, stressing the importance of reduced influx of CO2 as an important factor for drought-induced declines of photosynthesis. These results are discussed with respect to the occurrence of significant resistances in the leaf mesophyll, in addition to the stomatal resistances.
Keywords: chlorophyll fluorescence; chloroplasts; CO2 diffusion; Drought; mesophyll conductance; oaks; Stomatal conductance

Limitation of photosynthetic activity by CO2 availability in the chloroplasts of oak leaves from different species and during drought - Roupsard, O.; Gross, P.; Dreyer, E. (Ann. For. Sci., 1996)
It has recently been suggested that the low photosynthesis rates in tree species as compared to highly productive crops is at least partly due to resistances opposing the CO 2 fluxes in the mesophyll of tree leaves. To validate this assertion, values of CO2 mole fractions in the chloroplasts of leaves from Quercus petraea, Q robur, Q ilex and Populus sp were estimated on the basis of the analysis of the partitioning of light driven electron flow between fractions used for the carboxylation or the oxygenation of RuBP by Rubisco. The procedure used included: i) a measure of total light driven electron flows derived from the chlorophyll a fluorescence ratio ΔF/Fm', which is proportional to the photochemical efficiency of PS II, multiplied by incident irradiance and a calibration coefficient; ii) an estimation of the electron flux devoted to carboxylation obtained from net CO2 assimilation and respiration rate measurement, and using the known electron requirements (four electrons for CO2 or O2 fixation); iii) the derivation of the CO2 mole fraction in the chloroplasts from the specificity factor of Rubisco, and the ratio of carboxylation/oxygenation of RuBP. Results showed that in the absence of drought stress, the mole fraction of CO2 in the chloroplasts (35-45% of the atmospheric one) was much lower than the calculated substomatal one (60-70% of the atmospheric) in all species. Moreover, lowest values were recorded in the species with lowest assimilation rates, suggesting that the differences in the net CO 2 assimilation rate between species are linked to the CO2 availability in the chloroplasts. Finally, the CO2 availability decreased with increasing drought in the soil, stressing the importance of reduced influx of CO2 as an important factor for drought-induced declines of photosynthesis. These results are discussed with respect to the occurrence of significant resistances in the leaf mesophyll, in addition to the stomatal resistances.
Keywords: chlorophyll fluorescence; chloroplasts; CO2 diffusion; Drought; mesophyll conductance; oaks; Stomatal conductance